A Col I and BCP ceramic bi-layer scaffold implant promotes regeneration in osteochondral defects. Issue 7 (29th January 2019) - Cai, Hanxu; Yao, Ya; Xu, Yang; Wang, Qing; Zou, Wen; Liang, Jie; Sun, Yong; Zhou, Changchun; Fan, Yujiang; Zhang, Xingdong
Abstract : A new bi-layer scaffold composed of Col I and BCP ceramic was prepared to regenerate osteochondral defect. The result demonstrated the bi-layer scaffold could effectively promote the regeneration of both the cartilage and the subchondral bone layer. Abstract : Osteochondral defects occur in the superficial cartilage region, intermediate calcified cartilage, and subchondral bone. Due to the limited regenerative capacity and complex zonal structure, it is critically difficult to develop strategies for osteochondral defect repair that could meet clinical requirements. In this study, type I collagen (Col I) and BCP ceramics were used to fabricate a new bi-layer scaffold for regeneration in osteochondral defects. The in vitro studies showed that the bi-layer scaffold provided special functions for cell migration, proliferation and secretion due to the layered scaffold structure. The in vivo results demonstrated that the bi-layered scaffold could effectively promote the regeneration of both the cartilage and the subchondral bone, and the newly formed cartilage layer, with a similar structure and thickness to the natural cartilaginous layer, could seamlessly integrate with the surrounding natural cartilage and regenerate an interface layer to mimic the native osteochondral structure.